2015
DOI: 10.1155/2015/546210
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin Induces Mitochondria-Dependent Apoptosis in Pancreatic and Oral Cancer Cells by Downregulating hTERT Expression via Activation of the JNK/p38 Pathway

Abstract: Bufalin, a digoxin-like active component of the traditional Chinese medicine Chan Su, exhibits potent antitumor activities in many human cancers. Bufalin induces mitochondria-dependent apoptosis in cancer cells, but the detailed molecular mechanisms are largely unknown. hTERT, the catalytic subunit of telomerase, protects against mitochondrial damage by binding to mitochondrial DNA and reducing mitochondrial ROS production. In the present study, we investigated the effects of bufalin on the cell viability, ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Therefore, cancer treatment by means of enhancing intracellular ROS production may be considered an effective approach. Natural compounds, such as nimbolide and bufalin, are able to induce pancreatic cancer cell apoptosis by increasing ROS levels (31,32). The present study demonstrated that treatment with 25 µM moscatilin led to an increase in ROS generation; however, moscatilin-inhibited cell viability was abolished by NAC, thus suggesting that ROS is responsible for the proapoptotic effects of moscatilin on pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cancer treatment by means of enhancing intracellular ROS production may be considered an effective approach. Natural compounds, such as nimbolide and bufalin, are able to induce pancreatic cancer cell apoptosis by increasing ROS levels (31,32). The present study demonstrated that treatment with 25 µM moscatilin led to an increase in ROS generation; however, moscatilin-inhibited cell viability was abolished by NAC, thus suggesting that ROS is responsible for the proapoptotic effects of moscatilin on pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that T-oligo–initiated DDRs are specific to cancer cells and may be due to changes in telomere physiology that are common among cancers. Silencing hTERT in oral cancer cells is accompanied by caspase-9/-3 cleavage, DNA damage responses, and decreased cell viability [79]. It may be possible that T11’s antiproliferative response is in some way hTERT-dependent or hTERT-mediated due to its homology to the telomere, and therefore selective to cells that express the telomerase enzyme.…”
Section: Telomere Homolog Oligonucleotidesmentioning
confidence: 99%
“…The mitochondrial pathway consists of the main signal in cell apoptosis. [32][33][34] In the start-up phase, the mitochondria release cytochrome c, which activates the caspase family and then starts cascades in the cytoplasm. 35 To date, at least 15 members of the caspase family have been identified.…”
Section: Discussionmentioning
confidence: 99%